Copper‐Catalyzed Intermolecular Enantioselective Radical Oxidative C(sp3)−H/C(sp)−H Cross‐Coupling with Rationally Designed Oxazoline‐Derived N,N,P(O)‐Ligands - Liu, Lin; Guo, Kai‐Xin; Tian, Yu; Yang, Chang‐Jiang; Gu, Qiang‐Shuai; Li, Zhong‐Liang; Ye, Liu; Liu, Xin‐Yuan (Angewandte Chemie International Edition, 2021)
The intermolecular asymmetric radical oxidative C(sp3)−C(sp) cross‐coupling of C(sp3)−H bonds with readily available terminal alkynes is a promising method to forge chiral C(sp3)−C(sp) bonds because of the high atom and step economy, but remains underexplored. Here, we report a copper‐catalyzed asymmetric C(sp3)−C(sp) cross‐coupling of (hetero)benzylic and (cyclic)allylic C−H bonds with terminal alkynes that occurs with high to excellent enantioselectivity. Critical to the success is the rational design of chiral oxazoline‐derived N,N,P(O)‐ligands that not only tolerate the strong oxidative conditions which are requisite for intermolecular hydrogen atom ion (HAA) processes but also induce the challenging enantiocontrol. Direct access to a range of synthetically useful chiral benzylic alkynes and 1,4‐enynes, high site‐selectivity among similar C(sp3)−H bonds, and facile synthesis of enantioenriched medicinally relevant compounds make this approach very attractive. Chiral benzylic alkynes and 1,4‐enynes can be obtained in a straightforward approach from commercially available terminal alkynes and a diverse range of compounds containing benzylic and allylic C−H bonds by using the title reaction. The success of this approach lies in newly designed anionic N,N,P(O)‐ligands bearing a stable chiral oxazoline and a pentavalent phosphine oxide that are generated in situ.